INTERNATIONAL BUSINESS MARKETING IN FRANCE, INDONESIA, INDIA AND CHINA - Rico Nur Ilham; Hotma Nababan; Putri Nabilla; Dinda Putri Salsabila (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
In the current era of globalization where the rapid economic growth of every country, both developed and developing countries in the world, has created a tremendous demand pull, especially in densely populated countries such as France, Indonesia, India and China. On the other hand, computerization technology, communication, information, transportation and product innovation are increasingly sophisticated from time to time. This technological advancement has become one of the main drivers for world business to become increasingly global. In this study the authors used a descriptive qualitative research method, where this research method is based on the philosophy of postpositivism which is used to examine objects with natural conditions where the researcher is the key instrument (Sugiyono: 2012).